Caries-associated oral microbiome in head and neck cancer radiation patients: a longitudinal study. Issue 1 (1st January 2019) - Mougeot, Jean-Luc C.; Stevens, Craig B.; Almon, Kathryn G.; Paster, Bruce J.; Lalla, Rajesh V.; Brennan, Michael T.; Mougeot, Farah Bahrani
ABSTRACT: Head and neck cancer (HNC) therapy often leads to caries development. Our goal was to characterize the oral microbiome of HNC patients who underwent radiation therapy (RT) at baseline (T0), and 6 (T6) and 18 (T18) months post-RT, and to determine if there was a relationship with increased caries. HOMI NGS was used to determine the relative abundance (RA) of >600 bacterial species in oral samples of 31 HNC patients. The DMFS score was used to define patient groups with tooth decay increase (DMFS[+]) or no increase (DMFS[-]).A change in microbiome beta-diversity was observed at T6 and T18. The Streptococcus mutans RA increased at T6 in both DMFS[+] and DMFS[-] groups. The RA of Prevotella melaninogenica, the species often associated with caries in young children, decreased at T6 in the DMFS[-] group. The RA of the health-associated species, Abiotrophia defective, decreased in the DMFS[+] group. The oral microbiome underwent significant changes in radiation-treated HNC patients, whether they developed caries or not. Caries rates were not associated with a difference in salivary flow reduction between DMFS[+] andDMFS[-] groups. Patients who develop caries might be more susceptible to certain species associated with oral disease or have fewer potentially protective oral species.